Pengaruh Tingkat Efisiensi Distribusi Penjualan Produk Batik Pamekasan Dengan Metode Data Envelopment Analysis (DEA) - Mita Dwi Purwanti; Indra Cahyadi; Ika Deefi Anna (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
Batik Pamekasan is located in a small village so that buyer access is difficult, besides that it does not measure the efficiency level in each distribution area so that the profit is not optimal. The purpose of this study is to determine the level of efficiency of Pamekasan batik sales distribution using the Data Envelopment Analysis (DEA) method and provide suggestions for improvement in increasing the level of efficiency. The results obtained for the 100% efficient regions are DMU 4, DMU 5, DMU 6, DMU 7, DMU 8 range green. The inefficient regions are DMU 1, DMU 2, the efficiency score is 74.8%, 41.7% range red while DMU 3, DMU 9 the efficiency score is 90.99% range amber. Proposed improvements make rules limiting the purchase of batik products below 500 pieces for low quality, making centers close to customers so that access to purchases is easy and saves distribution costs.